Can tooth bleaching agents cause genotoxicity in the oral epithelium? A systematic review with meta-analysis (Research, Society and Development, 2022)
Objective: To assess, with a systematic review (SR) with meta-analysis, the occurrence of genotoxic effects on the oral epithelium after exposure to tooth bleaching agents. Material and methods: This review was performed according to the PRISMA protocols. To identify relevant studies, a systematic search was performed in the following electronic databases: PubMed, Scopus, Embase, LILACS, and Google Scholar. The research question was "Can tooth bleaching agents cause genotoxicity in the oral epithelium?”. The treatment effects were defined as the standardized mean difference (SMD) and 95% confidence intervals (CI) were established. Results: 154 studies were selected and, after screening titles and abstracts, seven full-text manuscripts were assessed for eligibility, of which four studies were included in the meta-analysis. There were no statistically significant differences in the frequency of micronuclei before and after exposure (SMD= -0.14, 95% CI, 0.98 to 0.60, p=0.74), with a Tau2 index = 1.00; Chi2 = 70.20; p-value